Social Media and Investment Decision of Gen Z in Nepali Capital Market - Sunar, Upendra; Thapa, Uttam Bahadur (The Management Review, 2026)
This study aims to examine the impact of social media on stock market investment decisions of Gen Z investors in Sudurpaschim Province, Nepal, specifically on informational and behavioral aspects. The research sought to determine the influence of usefulness, trust, and usage of social media on Gen Z investors, including the moderating effect of herding and overconfidence. The research used a quantitative research approach, where a structured questionnaire was used as a research instrument. The research participants were 220 Gen Z investors, aged 18-28 years. The findings were analyzed using SPSS software version 27 for multiple regression analysis, and Hayes PROCESS Macro version 4 for 5,000 bootstrap samples. The findings suggest that the model accounted for 50.2% of the variance of investment decisions (Adjusted R² = 0.502). The findings suggest that perceived usefulness is a significant factor for investment decisions (β = 0.342, p < 0.001), as is trust (β = 0.187, p = 0.003) and online community engagement (β = 0.168, p = 0.004). Frequency of use is, however, not significant for investment decisions (β = 0.066, p = 0.162). Herding and overconfidence partially mediate these relationships. The findings suggest that social media plays a role in investment decisions, and rational evaluation and behavioral biases of young investors cannot be ignored.